PERANCANGAN ALAT PEMBAYARAN SANTRI BERBASIS ESP32 PADA KOPERASI PONDOK PESANTREN AL-GHOZALI TAMBAKBERAS - Tholib Hariono; Miftakhul Ulum (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research was motivated by the problems of cash transactions in Islamic boarding school cooperatives, which are slow, prone to errors, difficult to monitor, and risky in terms of money loss. The purpose of this research is to design and develop a fast, accurate, and transparent non-cash payment system for the Al-Ghozali Tambakberas Islamic Boarding School Cooperative, while also facilitating the monitoring of student expenditures. The method used is prototyping, which includes communication of requirements, design, implementation, and black-box testing. The hardware developed consists of ESP32, RFID RC522, and a buzzer; the software uses Arduino IDE (firmware), PHP–MySQL (API and database), and a website for cashiers and admin panels. The transaction flow is carried out by tapping the RFID card; the system verifies the UID, automatically deducts the balance, records transactions in real-time, and provides feedback via the buzzer. Web features include card registration, cashier, transaction history and reports, balance top-up, and student balance monitoring. Test results show that all functions work well: accurate card reading, fast processing, consistent recording, and an easy-to-use interface. In conclusion, the system can improve the operational efficiency of the cooperative and the transparency of student financial management, making it suitable for implementation in Islamic boarding schools.